PENGEMBANGAN ALAT PERAGA HUKUM ARCHIMEDES UNTUK SISWA KELAS VIII SMP - Pratiwi, Eko Dian; Linuwih, Suharto (Physics Communication, 2017)
An experiment has been done on the development objects Archimedes law to increase the understanding of the concept. Archimedes law objects are as instructional media to explain the elusive concept of learners, especially on the concept of objects floating, sinking and floating. This is shown by the result of studentslearning to the concept of Archimedes law in SMP N 2 Batang in 2011/2012 class VIII, has not reached 85% of the limit value of 70 completed. The condition is possible because one of the reasons is that during this learning method is used less effective resulting for low student in understanding of concepts, so need a solution to improve learners' understanding of the concept of the law of Archimedes. Archimedes law objects that have been developed to influent the change patterns of thinking, so as to improve the understanding of the concept of learners. Archimedes law objects developed as a modification to the standard objects in variety of liquid and the test objects.